USULAN PENATAAN PEDAGANG KAKI LIMA DI KAWASAN LAPANGAN MERDEKA MEDAN - Gulo, Antonius Amonio; Aritonang, Emmy Ria; Naibaho, Polin (Unika Santo Thomas, 2018)
Merdeka Square is a public open space which is intended for all people. Public open space is a place as a general basis where people carry out functional and ritual activities that bind the community, both in the normal routine of daily life or in periodic celebrations. Merdeka Square is a place frequented by some of the citizens of Medan City. Even visitors from outside Medan came to take time to stop at Merdeka Square when certain events were held at Merdeka Square. This is what attracts people - certain people use the crowd to become the potential to run a business. So it is not surprising that in the Merdeka Square area at certain events and days it will be crowded not only with the presence of visitors to Merdeka Square, but also the presence of the informall sector such as street vendors. The purpose of this study is to obtain or produce a design proposal to organize the Street Vendors in the Merdeka Square Area in hopes of increasing comfort for visitors in the Merdeka Square Area.